2013
DOI: 10.1177/0194599813495815a47
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Duty Hour Regulation on Resident Surgical Case Volume in Otolaryngology

Abstract: Conclusions:The results support our hypothesis that obese patients do not have larger airways. Moreover, the results indicated a trend toward smaller airways as BMI increased. Specifically, as BMI increases, tracheal width appears to decrease. This information should help medical professionals avoid the tendency to use a larger tube to intubate an obese patient. Hopefully this will result in fewer airway injuries in a society where obesity has become an epidemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Fortunately, case numbers for all four key indicator procedures increased after duty hour restriction at TH‐OTO both in number and in percentage of the total. This finding correlates with a review of ACGME otolaryngology procedure logs over the same time period. Otolaryngology training spots accounted for 1.2% of resident positions throughout these time periods (244 positions in 2000 to 273 in 2008) .…”
Section: Discussionsupporting
confidence: 84%
“…Fortunately, case numbers for all four key indicator procedures increased after duty hour restriction at TH‐OTO both in number and in percentage of the total. This finding correlates with a review of ACGME otolaryngology procedure logs over the same time period. Otolaryngology training spots accounted for 1.2% of resident positions throughout these time periods (244 positions in 2000 to 273 in 2008) .…”
Section: Discussionsupporting
confidence: 84%
“…In a review of general surgery residents' ACGME case logs, Damadi et al observed a significant decline in the number of specialized cases recorded, but no change in the number of “bread and butter” procedures . Curtis et al similarly found no decrease in the number of assessed key‐indicator cases logged by otolaryngology residents . However, questions remain regarding the breadth and depth of residents' experience and their proficiency with less‐frequently performed otolaryngologic procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Feasibly, earlier exposure to basic and specialized otolaryngology procedures will allow resident assistant experience early, and thus earlier resident surgeon roles. After 2003 duty hour restrictions, otolaryngology case volume did not decrease, and resident key indicators numbers have actually increased since the change . Thus, continued monitoring of case volume and type will be an important metric following curriculum changes.…”
Section: Discussionmentioning
confidence: 99%